2015
DOI: 10.1038/ismej.2015.166
|View full text |Cite
|
Sign up to set email alerts
|

Food availability affects the strength of mutualistic host–microbiota interactions in Daphnia magna

Abstract: The symbiotic gut microbial community is generally known to have a strong impact on the fitness of its host. Nevertheless, it is less clear how the impact of symbiotic interactions on the hosts' fitness varies according to environmental circumstances such as changes in the diet. This study aims to get a better understanding of host-microbiota interactions under different levels of food availability. We conducted experiments with the invertebrate, experimental model organism Daphnia magna and compared growth, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
81
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 47 publications
13
81
1
Order By: Relevance
“…) followed by Aeromonadaceae , Arcicella , Flavobacteriaceae (Callens et al . ). Other studies have shown the microbiota of Daphniidae sp.…”
Section: Discussionmentioning
confidence: 99%
“…) followed by Aeromonadaceae , Arcicella , Flavobacteriaceae (Callens et al . ). Other studies have shown the microbiota of Daphniidae sp.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence mainly comes from studies comparing germ-free to conventionally reared individuals, in particular in arthropods, which reveal that gut bacteria have an overwhelming influence on growth, development, reproduction and survival. In the fruit fly Drosophila melanogaster (Storelli et al 2011) and in the water flea Daphnia magna (Sison-Mangus et al 2015, Callens et al 2016, germ-free individuals develop more slowly and are smaller than conventional animals, while in mosquitoes, axenic larvae fail to develop beyond the first instar (Coon et al 2014). In all these species, inoculating axenic larvae with gut bacteria can restore a normal developmental rate (Storelli et al 2011, Coon et al 2014, Callens et al 2016.…”
Section: The Gut Microbiota As Crucial Mediator Of Life-history Stratmentioning
confidence: 99%
“…In the fruit fly Drosophila melanogaster (Storelli et al 2011) and in the water flea Daphnia magna (Sison-Mangus et al 2015, Callens et al 2016, germ-free individuals develop more slowly and are smaller than conventional animals, while in mosquitoes, axenic larvae fail to develop beyond the first instar (Coon et al 2014). In all these species, inoculating axenic larvae with gut bacteria can restore a normal developmental rate (Storelli et al 2011, Coon et al 2014, Callens et al 2016. Mono-association studies in Drosophila (Shin et al 2011, Storelli et al 2011), mosquitoes (Coon et al 2014) and Daphnia (Peerakietkhajorn et al 2016) further identified single bacterial strains that are sufficient to recapitulate the natural microbiota growth-promoting effect.…”
Section: The Gut Microbiota As Crucial Mediator Of Life-history Stratmentioning
confidence: 99%
See 1 more Smart Citation
“…The hologenome theory provides functional explanations for the role of the microbiome in a Darwinian framework as it relates to speciation (Brucker and Bordenstein, 2012, 2013b) and potentially host fitness (e.g., Callens et al, 2016). A Lamarckian framework (Rosenberg et al, 2009), on the other hand, is complementary to this, as it details the mechanisms whereby microbes are acquired or lost during an organism's lifetime, and that the acquisition of a novel species or strain of microorganism may be integrated into the hologenome.…”
Section: Nature Of the Holobiontmentioning
confidence: 99%